2021
DOI: 10.1002/1878-0261.13145
|View full text |Cite
|
Sign up to set email alerts
|

FGF7–FGFR2 autocrine signaling increases growth and chemoresistance of fusion‐positive rhabdomyosarcomas

Abstract: Rhabdomyosarcomas are aggressive pediatric soft‐tissue sarcomas and include high‐risk PAX3–FOXO1 fusion‐gene‐positive cases. Fibroblast growth factor receptor 4 (FGFR4) is known to contribute to rhabdomyosarcoma progression; here, we sought to investigate the involvement and potential for therapeutic targeting of other FGFRs in this disease. Cell‐based screening of FGFR inhibitors with potential for clinical repurposing (NVP‐BGJ398, nintedanib, dovitinib, and ponatinib) revealed greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
3
1
0
Order By: Relevance
“…In contrast, FGF18, the third member of the FGF8 subfamily and a prognostic marker in some of the most aggressive adult epithelial cancers, 34 , 35 was not expressed in RMS cells at all. Expression of FGF7 in PF + ARMS cells was also significantly higher compared to PF−ERMS cells ( p = 0,015), as recently reported by others, 36 but similar to that measured in normal cells. FGF1 and FGF2, instead, two important family members with broad mitogenic activities in normal and pathological conditions, were expressed in tumor cell lines as much as in normal cells.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, FGF18, the third member of the FGF8 subfamily and a prognostic marker in some of the most aggressive adult epithelial cancers, 34 , 35 was not expressed in RMS cells at all. Expression of FGF7 in PF + ARMS cells was also significantly higher compared to PF−ERMS cells ( p = 0,015), as recently reported by others, 36 but similar to that measured in normal cells. FGF1 and FGF2, instead, two important family members with broad mitogenic activities in normal and pathological conditions, were expressed in tumor cell lines as much as in normal cells.…”
Section: Resultssupporting
confidence: 89%
“…Sensitivity to A.770041, AMG.706, ABT.888, AP.24534, AS601245, AUY922, and AZ628 was higher in the low-risk group than the high-risk group, while sensitivity to axitinib, A.443654, AG.014699, AICAR, Akt inhibitor VIII, and ATRA was higher in the high-risk group than the low-risk group. These drugs are commonly used in the clinical treatment of gliomas, and our results support their therapeutic value in this context ( Djuzenova et al, 2012 ; Yuan et al, 2018 ; Wang et al, 2021c ; Milton et al, 2021 ). In addition, these findings suggest the prospect of targeting lncRNAs in therapy for patients with gliomas.…”
Section: Discussionsupporting
confidence: 81%
“…Preliminary results of Dovitinib in NB cells, which express high levels of FGFR, indicated anticancer-activity in this tumor type [ 741 ]. Similar results were reported for RMS, albeit it was demonstrated that this inhibitor is not as potent as other FGFR inhibitors (i.e., ponatinib) [ 656 , 742 ]. In addition, due to its ability to cross the BBB, this compound has been indicated as a suitable candidate for the treatment of CNS tumors.…”
Section: Kinases As Druggable Targets—evidence and Limitationssupporting
confidence: 78%
“…Considering pediatric tumors, nintedanib has been shown to inhibit growth in EWS (A673, CHP100) and OS (SaOS2) cell lines, with a key role in controlling OS lung metastatic growth by blocking the fibrogenic reprogramming of OS stem cells (OSCs) [ 654 , 655 ]. Growth inhibition was also observed in a panel of 13 RMS cells, with the PAX3–FOXO1 fusion-gene-positive ones more sensitive to treatment [ 656 ]. Moreover, there are reports of EPN cells being sensitive to nintedanib treatment, while this drug is able to extend the survival of mice bearing ST-RELA xenografts [ 657 , 658 ].…”
Section: Kinases As Druggable Targets—evidence and Limitationsmentioning
confidence: 99%